The idea of a social cycle - Gene Callahan; Andreas Hoffmann (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2014)
The paper aims to explore what it means for something to be a social cycle, for a theory to be a social cycle theory, and to offer a suggestion for a simple, yet, we believe, fundamentally grounded schema for categorizing them. We show that a broad range of cycle theories can be described within the concept of disruption and adjustments. Further, many important cycle theories are true endogenous social cycle theories in which the theory provides a reason why the cycle should recur. We find that many social cycle theories fit with a two-population disruption and adjustment model similar to the well-known predator-prey model. This implies that a general modeling framework could be established for creating agent-based models of many social cycle theories.
Keywords: 330